Exclamatory Utterances in Harry Potter and The Sorcerer’s Stone Movie (2001): A Pragmatics Study - Ilham Erdianto Rosadi; Heri Heryono (Universitas Cokroaminoto Palopo, 2022)
This research is aimed to identify forms and examine the intentions exclamatory utterance that used in Harry Potter movie using grammatical rule for the forms and to describe the intentions used pragmatics speech act theory. Having analyzed the data and all the speakers of the utterances are all the actors in Harry Potter movies, there are founds five data of exclamatory utterance and the form namely as Word form, Noun phrase form, Verb phrase form, Adjectival phrase form, Simple sentence form, and compound sentence form. The speaker’s intentions are Command, Anger, Pleasure, Happiness, Surprised, Warning, Sadness, and Scared. In collecting the exclamatory utterance data with qualitative descriptive method which can be found in Harry Potter movies. The result from this research is found seven Command (28%), six Anger (24%), three Pleasure (12%), two Happiness (8%), two Surprised (8%), two Warning (8%), two Scared (8%), and one Sadness (4%).